2010
DOI: 10.1139/o09-173
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biogenesis of nuclear RNA polymerases?This paper is one of a selection of papers published in this special issue entitled “Canadian Society of Biochemistry, Molecular & Cellular Biology 52nd Annual Meeting — Protein Folding: Principles and Diseases” and has undergone the Journal's usual peer review process.

Abstract: More than 30 years of research on nuclear RNA polymerases (RNAP I, II, and III) has uncovered numerous factors that regulate the activity of these enzymes during the transcription reaction. However, very little is known about the machinery that regulates the fate of RNAPs before or after transcription. In particular, the mechanisms of biogenesis of the 3 nuclear RNAPs, which comprise both common and specific subunits, remains mostly uncharacterized and the proteins involved are yet to be discovered. Using prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 90 publications
6
27
0
Order By: Relevance
“…Notably, all three subunits of the TTT complex (TELO2, TTI1 and TTI2) did copurify with R2TP/PFDL subunits. As was the case in our initial experiments1819, protein components of all three RNAPs are among the strongest interactors of the R2TP/PFDL complex, as were a number of associated factors including RPAP2, SLC7A6OS and TANGO6, which have been shown to be involved in RNAP biogenesis and nuclear import333435.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Notably, all three subunits of the TTT complex (TELO2, TTI1 and TTI2) did copurify with R2TP/PFDL subunits. As was the case in our initial experiments1819, protein components of all three RNAPs are among the strongest interactors of the R2TP/PFDL complex, as were a number of associated factors including RPAP2, SLC7A6OS and TANGO6, which have been shown to be involved in RNAP biogenesis and nuclear import333435.…”
Section: Resultssupporting
confidence: 56%
“…Results of gel-based tandem affinity purification coupled to mass spectrometry (TAP-MS) of R2TP/PFDL subunits have been reported previously by our group1819 and although this dataset did identify interactions with all three RNA polymerases, no evidence was obtained that corroborated the connection to L7Ae RNPs or PIKKs. Over the past few years, advances in mass spectrometry technologies, modifications to our TAP-MS protocol28 and improvements to our computational analysis of protein–protein interactions2829 have made it possible to study purified complexes in solution from various cell fractions with limited starting material.…”
Section: Resultsmentioning
confidence: 59%
“…In humans, R2TP/Prefoldin-like complex contains Rpb5, a common subunit to the three eukaryotic RNA polymerases [2], as well as the unconventional prefoldin Rpb5 interactor (URI/RMP), a member of the prefoldin (PFD) family of ATP-independent molecular chaperones [8],[13]. URI physically binds Rpb5, other nuclear proteins involved in transcription, including the general transcription factor TFIIF [14][16] and components of the Paf-1 complex that promotes RNA pol II CTD phosphorylation and histone modification during transcription elongation [17].…”
Section: Introductionmentioning
confidence: 99%
“…URI was originally characterized in human and yeast cells as regulator of gene expression controlled by TOR (for target of Rapamycin) pathway [18]. Furthermore, URI has been linked to translation initiation [19], transcription regulation, chromatin stability or DNA damage response [13], [20]. URI is located mainly in the cytoplasm, although nuclear and perinuclear localization has also been observed in different organisms [20][22].…”
Section: Introductionmentioning
confidence: 99%
“…URI was originally identified as a protein binding the Rpb5 subunit of all three nuclear RNA polymerases (RNA pol) (5) and is considered to function as a scaffold protein able to assemble additional members of the PFD family in both human and yeast (2,3,6). Notably, we and others have demonstrated that Bud27 also binds Rpb5 in the three RNA polymerases (3,7).…”
Section: Introductionmentioning
confidence: 99%